Transport Infrastructure Effect on the Socio-Economic Development of a Region - L. V. Khudyakova (Вестник Научно-исследовательского института железнодорожного транспорта)
The paper tackles the identification aspect of transport infrastructure effect evidences on social sphere and economic development of the regions. The Republic of Sakha Yakutia was selected as an object of investigation. General approach and hypothesis employed by the investigation base on the thesis that transport infrastructure may be considered about as a prosperity factor attracting economic and non-economic benefits to a region and appearing for important determinant of socio-economic growth and rise in the living standards of its population. It has been shown that transport as economical system component has the potential of a powerful drive of social development contributing to increase in regional product and exchange of commodities and as a consequence to more efficient product specialization, wider spreading of innovative technologies, lower prices and higher quality of goods, higher benefits for their manufacturers and consumers, higher national wealth, higher levels of all sort of production and business activities, more efficient wildlands development, more efficient integration of new resources into economic turnover, other socio-economic benefits in the context of population living standards, its territorial mobility and human relations.